Business development strategy for the property sector after the COVID 19 pandemic in region-owned company subsidiaries of DKI Jakarta Province - Setiaji, Soleh; Maarif, Mohamad Syamsul; Asikin, Zenal (Indonesian Journal of Multidisciplinary Science, 2024)
The Covid-19 pandemic has led to a decline in property prices, with the property price index dropping from 209.8 points in 2019 to 187.43 points in 2020. The property sector in Indonesia is one of the sectors affected by a significant decline. Therefore, companies need to formulate business development strategies from the three business lines to improve their performance. The purpose of the study is to analyze internal and external factors that affect the business strategy of PT XYZ and to prioritize the most effective business development strategy for the company to adopt in response to changes in the property sector. The results of this research are expected to be applied as an alternative strategy in conducting business development in the future.